Improved tolerance of wheat plants (Triticum aestivum L.) to drought stress and rewatering by the arbuscular mycorrhizal fungus Glomus claroideum: Effect on growth and cell membrane stability - Beltrano, José (2008)
The aim of this paper was to investigate the contribution of the arbuscular mycorrhizal fungus Glomus claroideum to drought stress tolerance in wheat plants grown under controlled conditions in a growth chamber, and subjected to moderate or severe water stress and rewatering. Water stress tolerance was determined through total dry weight, leaf relative water content, leakage of solutes and leaf chlorophyll and protein concentrations in mycorrhizal and nonmycorrhizal wheat plants. Total dry weight and leaf chlorophyll concentrations were significantly higher in mycorrhizal plants after moderate or severe water stress treatments compared with non-mycorrhizal ones. Electrolyte leakage was significantly lower in water-stressed inoculated plants. Compared to non-inoculated plants, leaf relative water content and total protein concentration of inoculated individuals increased only under severe water stress. When irrigation was re-established, mycorrhizal plants increased their total dry weight and leaf chlorophyll concentration, and recovered cell membrane permeability in leaves compared with non-mycorrhizal plants. In conclusion, root colonization by G. claroideum could be an adequate strategy to alleviate the deleterious effects of drought stress and retard the senescence syndrome in wheat.